Transcription of a centromere-enriched retroelement and local retention of its RNA are significant features of the CENP-A chromatin landscape - B. J. Chabot; R. Sun; A. Amjad; S. J. Hoyt; L. Ouyang; C. Courret; R. Drennan; L. Leo; A. M. Larracuente; L. J. Core; R. J. O’Neill; B. G. Mellone (Genome Biology)
Abstract Background Centromeres depend on chromatin containing the conserved histone H3 variant CENP-A for function and inheritance, while the role of centromeric DNA repeats remains unclear. Retroelements are prevalent at centromeres across taxa and represent a potential mechanism for promoting transcription to aid in CENP-A incorporation or for generating RNA transcripts to maintain centromere integrity. Results In this study, we probe into the transcription and RNA localization of the centromere-enriched retroelement G2/Jockey-3 (hereafter referred to as Jockey-3) in Drosophila melanogaster, currently the only in vivo model with assembled centromeres. We find that Jockey-3 is a major component of the centromeric transcriptome and produces RNAs that localize to centromeres in metaphase. Leveraging the polymorphism of Jockey-3 and a de novo centromere system, we show that these RNAs remain associated with their cognate DNA sequences in cis, suggesting they are unlikely to perform a sequence-specific function at all centromeres. We show that Jockey-3 transcription is positively correlated with the presence of CENP-A and that recent Jockey-3 transposition events have occurred preferentially at CENP-A-containing chromatin. Conclusions We propose that Jockey-3 preferentially inserts at the centromere to ensure its own selfish propagation, while contributing to transcription across these regions. Given the conservation of retroelements as centromere components through evolution, our findings may offer a basis for understanding similar associations in other species.